Transforming Higher Education for Sustainable Development: Integrating the Sustainable Development Goals into University Systems - Erik Johansson (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2013)
The Sustainable Development Goals (SDGs) represent a global framework for addressing complex social, economic, and environmental challenges facing humanity. Higher education institutions play a critical role in achieving these goals by shaping future leaders, generating knowledge, and promoting sustainable innovation. However, many universities continue to operate within traditional educational models that are insufficient to address contemporary global challenges. This article examines how higher education institutions can integrate the SDGs into their institutional strategies, teaching practices, and research agendas. Drawing on interdisciplinary literature from education, sustainability studies, and policy analysis, the study explores key approaches for embedding sustainability principles within university systems. The analysis highlights three critical dimensions: curriculum transformation, research innovation, and institutional governance aligned with sustainability values. The article argues that universities must move beyond symbolic commitments to sustainability and instead adopt systemic changes that integrate the SDGs into academic culture and practice. By promoting interdisciplinary learning, community engagement, and ethical leadership, higher education institutions can contribute significantly to global sustainable development. The study concludes that transforming higher education is essential for preparing future generations to address the complex challenges outlined in the SDGs.